2016
DOI: 10.1016/j.sjbs.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of cadmium stress in Solanum lycopersicum L. by arbuscular mycorrhizal fungi via induction of acquired systemic tolerance

Abstract: Experiments were conducted to evaluate cadmium (Cd) stress-induced changes in growth, antioxidants and lipid composition of Solanum lycopersicum with and without arbuscular mycorrhizal fungi (AMF). Cadmium stress (50 μM) caused significant changes in the growth and physio-biochemical attributes studied. AMF mitigated the deleterious impact of Cd on the parameters studied. Cadmium stress increased malonaldehyde and hydrogen peroxide production but AMF reduced these parameters by mitigating oxidative stress. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(65 citation statements)
references
References 60 publications
6
56
0
Order By: Relevance
“…Because Cd is a non-essential element in plants, excessive Cd absorbed in plants directly influences their normal physiological function. The symptoms are usually characterized by growth inhibition, leaf chlorosis, metabolic block, and even plant death (Abd Allah et al, 2015; Hashem et al, 2016). Moreover, the absorbed Cd can poison other organisms, including humans, along the food chain (Amna et al, 2015; Tauqeer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because Cd is a non-essential element in plants, excessive Cd absorbed in plants directly influences their normal physiological function. The symptoms are usually characterized by growth inhibition, leaf chlorosis, metabolic block, and even plant death (Abd Allah et al, 2015; Hashem et al, 2016). Moreover, the absorbed Cd can poison other organisms, including humans, along the food chain (Amna et al, 2015; Tauqeer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…MDA is a well-known index for oxidative stress severity and the elevation of MDA indirectly indicates an increase in ROS. The increase in MDA content in Cd-stressed plants was observed in a number of plant studies (Hashema et al, 2016). The accumulation of MDA, which is the decomposition product of polyunsaturated fatty acids of bio-membranes refer to the insufficiency of suitable antioxidant system to overcome the over-production of ROS generated under cadmium stress.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies on spore morphology carried out in Saudi Arabia showed that AMF associated with A. ehrenbergiana and A. gerrardii were assigned only to Glomus and Claroideoglomus genera [16,18]. The genus Glomus was the most dominant followed by Acaulospora, Gigaspora, Claroideoglomus, and Scutellospora.…”
Section: Discussionmentioning
confidence: 96%
“…The genus Glomus was the most dominant followed by Acaulospora, Gigaspora, Claroideoglomus, and Scutellospora. The predominance of Glomus species in most ecosystems of Saudi Arabia [18], Senegal [14,45], China [46], and central Europe [47] suggests a better adaptation of this genus fungi to diverse environmental conditions such as drought, cold, and salinity [48]. Other reports [49,50] show that the dominance of fungi of the Glomus and Acaulospora genera was related to their sporogenous characteristics, especially the production of small spores within a short period of time compared with other genera such as Gigaspora and Scutellospora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation